Serotype and mating type characterization of Cryptococcus neoformans by Multiplex PCR Caracterização de sorotipo e "mating type" de Cryptococcus neoformans por PCR Multiplex - Vívian Gonçalves Carvalho; Mateus Souza Terceti; Amanda Latercia Tranches Dias; Claudete Rodrigues Paula; Juliana Pereira Lyon; Antônio Martins de Siqueira; Marília Caixeta Franco (Revista do Instituto de Medicina Tropical de São Paulo, 2007)
Cryptococcus neoformans is an encapsulated yeast, etiological agent of cryptococcosis. The species is commonly associated with pigeon droppings and plant materials. The aim of the present work was to verify the presence of the yeast in pigeon droppings, and to identify the isolates obtained in serotypes and mating types (MAT). Ten samples of pigeon droppings were collected in the rural area of the city of Alfenas, Brazil. Samples were inoculated in agar Niger medium for fungal isolation and 22 isolates with characteristics of C. neoformans were obtained. The serotypes and MAT were determined by multiplex PCR using specific primers. Serotypes were also determined by using the Kit Crypto Check. Among the 22 samples evaluated, eight were identified as C. neoformans by classic identification tests. These samples were characterized as serotype A by the Kit Crypto check and as serotype A MAT alpha by the multiplex PCR. The present study reinforces the evidence that pigeon droppings are a reservoir for C. neoformans and confirms the prevalence of C. neoformans var. grubii (Aalpha) among environmental isolates. It also demonstrates that multiplex PCR is an acceptable alternative for serotype analysis because it reduces the costs for each reaction and analyses serotype and MAT simultaneously. Cryptococcus neoformans é levedura encapsulada, agente etiológico da criptococose. As espécies são comumente associadas com fezes de pombos e material vegetal. O objetivo do presente trabalho foi verificar a presença de leveduras em fezes de pombos e identificar os isolados em relação aos sorotipos e "mating types". Dez amostras de fezes de pombos foram coletadas na zona rural da cidade de Alfenas, Brasil. As amostras foram inoculadas em agar Niger e 22 isolados com características de C. neoformans foram obtidos. Os sorotipos e "mating types" foram determinados pela PCR multiplex e os sorotipos foram identificados também pelo Kit Crypto Check. Dentre as 22 amostras avaliadas, oito foram identificadas como C. neoformans através dos ...